1993
DOI: 10.1095/biolreprod49.4.831
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Food Restriction on Neuropeptide-Y, Proopiomelanocortin, and Luteinizing Hormone-Releasing Hormone Gene Expression in Sheep Hypothalami1

Abstract: Chronic food restriction decreases secretion of LH as a result of inhibitory influences on secretion of LHRH. We have previously reported that neuropeptide-Y (NPY) may directly or indirectly mediate this inhibitory effect on LHRH secretion. In the study reported here, we tested the hypothesis that long-term food restriction suppresses tonic release of LH as a result of 1) an increase in biosynthetic activity of NPY neurons in the arcuate nucleus of the hypothalamus, 2) an increase in activity of neurons that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
61
0
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(78 citation statements)
references
References 54 publications
(74 reference statements)
15
61
0
2
Order By: Relevance
“…It is tempting to speculate that the melanocortin pathway may be implicated in driving photoperiodinduced appetite cycles in the ram and/or in mediating the testosterone amplification of these cycles. In addition, the present data indicated that testosterone might also be implicated in amplifying the POMC response to negative energy balance, since POMC mRNA was down-regulated by R compared with AL, in agreement with published sheep data (McShane et al 1993), but this response was seen only in rams and only in SD.…”
Section: Nutritional Status and Hypothalamic Gene Expression · Z A Arsupporting
confidence: 92%
“…It is tempting to speculate that the melanocortin pathway may be implicated in driving photoperiodinduced appetite cycles in the ram and/or in mediating the testosterone amplification of these cycles. In addition, the present data indicated that testosterone might also be implicated in amplifying the POMC response to negative energy balance, since POMC mRNA was down-regulated by R compared with AL, in agreement with published sheep data (McShane et al 1993), but this response was seen only in rams and only in SD.…”
Section: Nutritional Status and Hypothalamic Gene Expression · Z A Arsupporting
confidence: 92%
“…Taken together, these results suggest that there are both positive and negative regulators of GHRH expression in the fasted state, where under certain physiologic conditions the balance between these regulators can be skewed to favor GHRH synthesis. This logic is supported by the report of Henry et al (2001), who observed that food restriction in the ovariectomized ewe, which increases NPY mRNA (McShane et al 1993), also increased GHRH mRNA.…”
Section: Seungjoon Park and Others · Effects Of Fasting On The Gh-axisupporting
confidence: 63%
“…Previous in situ hybridisation studies have shown that long-term food restriction increases the expression of the orexigenic peptide neuropeptide Y (NPY) in ewe lambs (McShane et al 1993) and in gonadectomised sheep (Adam et al 1997, Henry et al 2000. Expression of another orexigenic peptide, melaninconcentrating hormone (MCH), is also increased in under-fed ovariectomised ewes (Henry et al 2000).…”
Section: Discussionmentioning
confidence: 99%